Bit Coin Prediction Using Machine Learning (International Journal of Psychosocial Rehabilitation, 2020)
Machine learning is very fast in processing any dataset. Prediction of Bitcoin is most widely done to maintain the transactions in cryptocurrency. Machine learning is mostly attracted by the trading that has gained interest over the past few years. This approach is used to test the theory that the failures of the cryptocurrency market can be exploited to generate abnormal profits. In this paper, mainly the proposed system analyzed the dataset consisting of Bitcoin historical data from December 1st, 2014, to January 8th, 2018, divided into one-minute increments. This time frame consists of 1,574,274 minutes. In this paper, the proposed machine learning algorithm is used to predict the bitcoin and analyze the transactions. The resultML-AI shows the performance of the proposed system.